Development of Learning Media for Luwu Folklore E-Book Based on Flipbook Maker on Material Habituating Commendable Morals Class VIII Mts Cimpu - Andi Isratul Fadilah; Andi Riawarda (Journal of Indonesian Islamic Studies, 2024)
This research is designed to develop learning media for the Luwu Folklore e-Book in the subject of moral beliefs material to familiarize commendable morals in grade VIII MTsS Cimpu. This research uses a 4D development model which includes the steps: Difine, Design, Develop and Disseminate. The validity of this media has been tested by experts in materials, language and media. The validation results from material experts recorded a high percentage of 100%, while linguists gave a percentage of 69%, and media experts obtained a percentage of 86%. Each of them is in the high category. This shows that the Luwu Folklore e-Book is very worthy of being used as a learning medium in the material of habituating commendable morals in class VIII MTsS Cimpu.